2004
DOI: 10.1021/jm030558s
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Conformational and Positional Adaptability in Structure-Based Design of TMC125-R165335 (Etravirine) and Related Non-nucleoside Reverse Transcriptase Inhibitors That Are Highly Potent and Effective against Wild-Type and Drug-Resistant HIV-1 Variants

Abstract: Anti-AIDS drug candidate and non-nucleoside reverse transcriptase inhibitor (NNRTI) TMC125-R165335 (etravirine) caused an initial drop in viral load similar to that observed with a five-drug combination in naïve patients and retains potency in patients infected with NNRTI-resistant HIV-1 variants. TMC125-R165335 and related anti-AIDS drug candidates can bind the enzyme RT in multiple conformations and thereby escape the effects of drug-resistance mutations. Structural studies showed that this inhibitor and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
492
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(533 citation statements)
references
References 52 publications
18
492
1
2
Order By: Relevance
“…Five RT crystal structures (1suq, 1sv5, 1s6q, 1s9e, 1s6p) [13] were analysed to investigate the extent of protein-ligand motion over the sampling time of the dynamics simulation. These crystal structures were selected due to their good resolution (average of 2.87 Å) and complete sequence of residues, allowing simulations to be performed on structures that did not need to be artificially completed.…”
Section: Methods Development Stability Of Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Five RT crystal structures (1suq, 1sv5, 1s6q, 1s9e, 1s6p) [13] were analysed to investigate the extent of protein-ligand motion over the sampling time of the dynamics simulation. These crystal structures were selected due to their good resolution (average of 2.87 Å) and complete sequence of residues, allowing simulations to be performed on structures that did not need to be artificially completed.…”
Section: Methods Development Stability Of Crystal Structuresmentioning
confidence: 99%
“…The length of the molecular dynamics simulation was chosen such that the total energy and root mean square difference (RMSD) * had both appeared to reach equilibrium during the production step (an observed plateau over the last 0.025 ns). The structure chosen for the calibration of simulation time was 1s6p, which is crystallized with ligand 1 known to have high activity against native HIV-RT, but poor activity against strains with common mutations [13].…”
Section: Calibration Of Simulation Timementioning
confidence: 99%
“…Interestingly, this HIV-1 RT catalytic feature leads to the emergence of mutations at a frequency of about 104 per cycle (Arts & Le Grice, 1998;Patel et al, 1995;Ehteshami & Goette, 2008). Importantly, this high rate of mutation significantly conserves the biological activities of HIV-1 RT, while simultaneously conferring a multidrug-resistant profile to the virus (Das et al, 2004;Martinez-Picado & Martínez, 2008).…”
Section: Hiv-1 Reverse Transcriptase (Hiv-1 Rt) -Still An Effective Tmentioning
confidence: 99%
“…The inhibition mechanism is due to the expansion of the region of NNBIP, since this hydrophobic "pocket" is closed during the active period of TR. The opening of this region involves a large displacement of the aromatic side chains of Tyr181, Tyr188 and Trp229 and a rotation of the leaves β-β-12-13-β-14, resulting in a breakdown of the primer grip in the direction that the complex primertemplate moves during the subsequent incorporation of nucleotides (Das et al, 2004) (Figure 3). Our group showed that the diterpene 8,10,18-trihydroxy-2,6-dolabelladiene (THD, 5), obtained from the extract of Dictyota pfaffi or by reducing 10,18-diacetoxy-8-hydroxy-2,6-dolabelladiene (3), showed signifi cant antiviral activity, up to 3 times higher with this chemical modifi cation (Barbosa et al, 2003;Barbosa et al, 2004;Cirne-Santos et al, 2006).…”
Section: Terpenes As Nnrti Models: Looking At Future Anti-hiv Treatmementioning
confidence: 99%
“…HIV-1 non-nucleoside reverse transcriptase inhibitors (NNRTIs) have become an essential part of HAART, with unique antiviral high potency, low toxicity and exquisite selectivity 4 . Among the NNRTIs, diaryl triazine (DATA) derivatives (Figure 1), such as R129385, R120394 and R106168 displayed high potent activity against wild-and NNRTI-resistant strains of HIV-1 which has attracted considerable attention over the past few years 5 . The development of hybrid molecules through the arrangement of dissimilar pharmacophores may provide compounds with attractive biological profiles 6 .…”
Section: Introductionmentioning
confidence: 99%